Antiangiogenic nanotherapy with lipase-labile Sn-2 fumagillin prodrug. (October 2012) - Pan, Dipanjan; Sanyal, Nibedita; Schmieder, Anne H; Senpan, Angana; Kim, Benjamin; Yang, Xiaoxia; Hu, Grace; Allen, John S; Gross, Richard W; Wickline, Samuel A; Lanza, Gregory M
Background: The chemical instability of antiangiogenic fumagillin, combined with its poor retention during intravascular transit, requires an innovative solution for clinical translation. We hypothesized that an Sn-2 lipase-labile fumagillin prodrug, in combination with a contact-facilitated drug delivery mechanism, could be used to address these problems.Methods: αv β3 -targeted and nontargeted nanoparticles with and without fumagillin in the prodrug or native forms were evaluated in vitro and in vivo in the Matrigel™ (BD Biosciences, CA, USA) plug model of angiogenesis in mice.Results: In vitro experiments demonstrated that the new fumagillin prodrug decreased viability at least as efficacious as the parent compound, on an equimolar basis. In the Matrigel mouse angiogenesis model, αv β3 -fumagillin prodrug decreased angiogenesis as measured by MRI (3T), while the neovasculature was unaffected with the control nanoparticles.Conclusion: The present approach resolved the previously intractable problems of drug instability and premature release in transit to target sites. Original submitted 1 September 2011; Revised submitted 30 December 2011; Published online 18 June 2012